(untitled) - UNFPA Vietnam (Ha Noi, 2009)
This report provides a comprehensive picture and analysis of the increasingly imbalanced sex ratios at birth occurring in Viet Nam. The report notes that if the sex ratio imbalance continues to increase after 2010, there will be a great impact on men who are born after 2005 and would be entering their marriageable age from 2030 onwards, because they would find themselves in much higher numbers than women their age
Keywords: Gender identity,Sex ratio,Sex preselection,Tỷ lệ giới tính,Lựa chọn giới tính; Vietnam,Vietnam,Việt Nam,Việt Nam